X-Ray Polarimetric Observations of the Western Hotspot of Pictor A - Stefano Tugliani; Francesco Massaro; Michela Negro; Raffaella Bonino; Nicolò Cibrario; Luca Latronico; Simone Maldera; Alessandro Paggi; Andrea Tramacere; Eileen T. Meyer; Ioannis Liodakis; Herman L. Marshall; et al. (The Astrophysical Journal Letters)
We present the results of the analysis of a ∼2 Msec spectropolarimetric observation of the western hotspot (WHS) of the radio galaxy Pictor A. This is the brightest extragalactic radio source that allows us to carry out spatially resolved observations using the Imaging X-ray Polarimetry Explorer (IXPE) because its WHS is located at ∼250″ from the radio core. The Pictor A WHS can be detected with IXPE as a pointlike source, with very low contamination from the nuclear emission, and it is extremely polarized at both radio and optical frequencies, where its emission is well described as synchrotron radiation. We find no X-ray polarization for the Pictor A WHS. However, the derived upper limit allows us to set a first constraint on the radiative processes occurring therein, ruling out a simple synchrotron scenario where particles, with a random distribution of pitch angles, radiate in a uniform magnetic field. We also tested a scenario with a random magnetic field compressed along the jet direction.